Motivation theory for elite karate athletes: A psycho-physiological approach - Galloway, S. (Human Movement, 2004)
Purpose The purpose of this study was to distinguish whether or not the use of Borg's rating of perceived exertion RPE [1] as a goal setting measure would lead to increased self-confidence levels. Each competitor was measured using Vealey's Trait and State Self-Confidence scales, TSCI and SSCI [2]. There were also questions used to further understand the dynamic within motivation theory.